An innovative approach to extend the shelf life of cottage cheese curds using food grade CO2‐α‐cyclodextrin complex powder: A preliminary study. Issue 2 (20th October 2017) - Ho, Thao M.; Howes, Tony; Bhandari, Bhesh R.
Abstract: The use of CO2 ‐α‐cyclodextrin complex powder to hinder mold and yeast growth in cottage cheese was investigated. The powder was directly mixed into the curds before packaging to achieve different CO2 concentrations (300, 600, and 900 ppm, mg CO2 /kg curd), followed by storing the samples at 7 and 25 °C for up to 6 weeks. The sample containers were opened to expose them to air for 15–20 min every week. The results showed the mold and yeast growth was significantly inhibited without affecting pH and moisture content of the curds. At 25 °C, mold and yeast growth occurred in the control samples (0 ppm CO2 ) at Day 5 while the samples with 300, 600, and 900 ppm CO2 were spoiled at Days 8, 9, and 10, respectively. At 7 °C, except for the control spoiled at Day 30, no mold and yeast were observed in other samples at the end of storage period. Practical applications: This study provided an innovative and simple approach to introduce CO2 gas in the encapsulated powder form for modified atmosphere packaging of cottage cheese. This can simply be done by mixing CO2 powder into cottage cheese prior to packaging, by which CO2 gas will be distributed throughout the product. During storage, due to effects of water in cottage cheese, the complex releases CO2 slowly so that spoilage microorganisms especially mold and yeast growth, were significantly prohibited.